Comparison of echocardiographic measurements and cardiac biomarkers in healthy dogs eating nontraditional or traditional diets. (8th December 2022) - Owens, Eric J.; LeBlanc, Nicole L.; Freeman, Lisa M.; Scollan, Katherine F.
Abstract: Background: There has been a recent association between nontraditional diets and development of diet‐associated dilated cardiomyopathy (DCM) in dogs. Hypothesis/Objectives: To compare echocardiographic measurements and cardiac biomarkers between healthy dogs eating nontraditional vs traditional diets. We hypothesized that dogs eating nontraditional diets would have lower measures of systolic myocardial performance compared to dogs eating traditional diets. Animals: Forty‐six healthy dogs: 23 eating nontraditional diets and 23 eating traditional diets. Methods: Prospective, cross‐sectional study. Dogs were divided into groups based on diet ingredients. Dogs underwent 2‐dimensional (2D), 3‐dimensional (3D), and Doppler echocardiographic examinations and analysis of plasma N‐terminal prohormone of B‐type natriuretic peptide, serum cardiac troponin I, and whole blood and plasma taurine concentrations. Results: Mean 2D ejection fraction (EF) was lower for dogs eating nontraditional diets (48.65 ± 7.42%) vs dogs eating traditional diets (56.65 ± 4.63%; P < .001; mean difference 8.0% [4.0%‐12.0%] 95% confidence interval [CI]). Mean 3D EF was lower for dogs eating nontraditional diets (45.38 ± 7.35%) vs dogs eating traditional diets (57.58 ± 4.84%; P < .001; 12.0% [8.0%‐16.0%] 95% CI). Mean 2D left ventricular end‐systolic volumes, indexed to body weight, were significantly higher in dogs eating nontraditional diets (1.46 ± 0.08 mL/kg) vs dogs eating traditional diets (1.06 ± 0.08 mL/kg; P = .002; 0.4 mL/kg [0.18‐0.62 mL/kg] 95% CI). Conclusions and Clinical Importance: Healthy dogs eating nontraditional diets had lower indices of systolic function and larger left ventricular volumes compared to dogs eating traditional diets. Screening of apparently healthy dogs eating nontraditional diets might allow for early detection of diet‐associated DCM.